2007
DOI: 10.1177/0145721707303807
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Eating Practices

Abstract: Purpose-The purpose of this study was to explore the perceptions of healthy eating by youth with diabetes as well as facilitators of and barriers to healthy eating behavior.Methods-One hundred forty youth aged 7 to 16 years with diabetes participated in 18 focus groups. Sample race/ethnicity was 71% white, 18% African American, 6% Hispanic, and 5% other; 69% of the participants were female.Results-Healthy eating was defined primarily in terms of eating fruits and vegetables, low fat, low sugar, and eating to k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 24 publications
(24 reference statements)
2
34
0
Order By: Relevance
“…Some children were able to list specific healthy effects [31,33,36,52]. Hill et al (1998) reported that dietary knowledge increased by age in New Zealand [32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some children were able to list specific healthy effects [31,33,36,52]. Hill et al (1998) reported that dietary knowledge increased by age in New Zealand [32].…”
Section: Resultsmentioning
confidence: 99%
“…Some children said that the choice of fruit in school was limited to canned fruit salad which they did not like or, as for the diabetic children in the study by Gellar et al (2007) they could not eat it because it was "drenched in sugary syrup" [27,31,32]. …”
Section: Resultsmentioning
confidence: 99%
“…1 Although dietary intake is an integral part of diabetes management, 35 previous research suggests that families of youth with T1D may not prioritize healthful eating, given the multiple demands of diabetes management, as well as barriers to healthy eating such as the widespread availability of unhealthy foods, lack of food preparation time and desire for intakes consistent with friends given the already substantial differences placed upon the youth with diabetes compared with their peer group. 19,36 In addition, some families may focus on a food’s postprandial glycemic response, emphasizing both the amount of carbohydrate and ease of carbohydrate estimation, which may limit the foods children with T1D choose to eat. 36 …”
Section: Discussionmentioning
confidence: 99%
“…18 Given the intense burden of T1D management for youth and their parents, including monitoring blood glucose, estimating carbohydrate intake, administering insulin and responding to blood glucose fluctuations, families may find recommendations for healthful eating to be less salient. 19 At a time when all youth struggle with physical, personal and social changes, adherence to dietary recommendations can be especially difficult for youth with T1D. 15 Food neophobia and pickiness may further complicate adherence to overall diabetes management, potentially impacting glycemic control; however, no research has examined these associations.…”
Section: Introductionmentioning
confidence: 99%
“…One study 22 of 108 urban Costa Rican adolescents found that adolescent boys were peer pressured to eat unhealthy foods as a sign of masculinity, where as adolescent girls were peer pressured to eat healthy foods as a sign of femininity. In another study 21 conducted with 140 adolescents with type 1 diabetes investigating perceptions, barrier and motivation to healthy eating, peer relationships were cited as a barrier to healthy eating and peer interactions were found to increase social pressure to eat unhealthy foods. In contrast, French et al 20 investigated potential motivating factors for vending snack choices in 418 adolescents and found peer influence was the least cited motivator for snack choice.…”
Section: Discussionmentioning
confidence: 99%